A critique to the article “Pina PSS, Mendes AT, Correa L, Coracin FL, de Sousa SCOM. The role of exfoliative cytology in diagnosis of oral lesions. Clin Oral Investig. 2024 Dec 6;29(1):2. doi: 10.1007/s00784-024-06080-9. PMID: 39641812.” - Pelin Güneri; Gaye Bolukbasi (Clinical Oral Investigations, 2025)
Objective This study investigated the impact of the Sudanese smokeless tobacco Toombak on cultivable oral bacteria, its potential antibacterial properties, and its own microbial composition. Materials and methods Oral swabs from 20 adult male participants, including ten long-term Toombak users and ten non-users, were analyzed through microbial inoculation and identification techniques. In addition, Toombak samples were examined for viable microorganisms, tested for antibacterial activity against selected reference strains, and the results were statistically analyzed using the Wilcoxon rank-sum test (α = 0.05). Results The overall bacterial counts, diversity, and species distribution showed no statistically significant differences between users and non-users, with the exception of Schaalia odontolytica (p = 0.0306) and the proportion of Gram-positive rods (p = 0.0137) expressed as percentages, which were more frequent in the control group. Toombak itself harbored mainly Bacillus spp., and no inhibitory activity against the tested bacteria was observed. While a non-significant trend toward lower bacterial counts was observed in Toombak users (1.83 × 10⁸ vs. 3.31 × 10⁸ CFU/ml), this finding should be interpreted cautiously given the exploratory design and substantial interindividual variability. Conclusion Further studies using larger cohorts and culture-independent methods are warranted to better clarify its microbial impact.